Impact of the Village Fund Policy on Community Economic Empowerment during the Covid-19 Pandemic - Rita Martini; Zulkifli Zulkifli; Sulaiman Sulaiman; Kartika Rachma Sari; Sukmini Hartati; Tri Anggun Pratiwi (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The goal of this study is to determine the effectiveness of village budget policies in community economic empowerment during the Covid-19 pandemic by analyzing the implementation of village funds. Design/methodology/approach: The data was analyzed using qualitative descriptive analysis with village leaders and officials. Findings: According to the findings of this study, the implementation of the village fund policy in Pangkul village during the Covid-19 period went off without a hitch. The allocation of village fund budgets in empowering economic communities in Pangkul village was quite effective. People in Pangkul Village were educated on the Covid-19 pandemic. Practical implications: Pangkul Village has also developed a new program, namely a resilient village, in order to keep its community stable and maintained in the face of the Covid-19 pandemic. Paper type: Research paper